From media technologies to mediated events: a different settlement between media studies and science and technology studies. Issue 8 (3rd July 2019) - Moats, David
ABSTRACT: There have been many recent attempts to bring insights from science and technology studies (STS) into media disciplines, many of which associate this work with materiality and technology, while existing media theories are used to analyse the domain of media content and political economy. While this is a reasonable settlement, in this paper I will suggest an alternative arrangement based around controversies. Controversies, and related empirical objects, can help break down dichotomies like producer/audience, social/technical, content/material and also provoke questions such as 'which media technologies matter in a given case?' However, controversies are often specific to science so I propose a type of study based around 'mediated events' (drawing on the work of Isabelle Stengers). I illustrate this with the case of the Woolwich attacks on Twitter. While this approach does not deliver a comprehensive theory of the media, it proposes a new settlement between STS and media studies, grounded in the empirical rather than high theory.